Diskresi Kepolisian dalam Pemberantasan Tindak Pidana Narkotika (Study Kasus Di Wilayah Hukum Polsek Padangbai Karangasem) - Anak Agung Gde Mahardi Prana; I Made Minggu Widyantara; Luh Putu Suryani (Jurnal Analogi Hukum, 2019)
Abstract In the current narcotics case the circulation is wide and the modus operandi is increasingly diverse, the police are required to develop their own law enforcement. With the descriptive theory and description of the practice of disclosing narcotics networks. Polri is expected to further spur members to improve the quality of their human resources, improve supervision of performance in the field, so that the implementation of discretion remains in the legal path. Thus, there will be growing public trust in the police institution, where the community voluntarily becomes a police partner in creating security and order. The police statement on narcotics eradication will theoretically spur police institutions to increase the intellectual capacity of their members to use common sense in acting. Illegal circulation of narcotics and corruption is a new dimension of crime, which requires serious handling. Formulation of the problem in this study: how the steps of the police reveal the drug network and how to eradicate drugs with the concept of discretion. The type of research used is the type of empirical research. The results of the discussion in this study are as follows: Police steps to uncover the drug network begins with: a) Call letter, b). Arrest, Search and Confiscation, c). Examination and d). Detention. Eradicating drugs with the concept of discretion as the executor of the unit of investigation and investigation of drug crimes, the drug work unit working on the basis of the standard was determined by the National Police Chief based on police reports. The guidelines for implementing or implementing the various principles are the steps of the police in uncovering drug networks. The steps to control and control not only control the police's personal supervision to early conduct a selection of his actions, but also his fellow colleagues and the seriousness of the police institution to take action against the police who abuse the discretion, under any pretext. Therefore the standard of operation becomes more important to realize so that there are measures to minimize discretionary deviations. Keywords: Discretion; Narcotics; Police Abstrak Dalam kasus narkotika saat ini peredarannya luas dan modus operandinya semakin beragam, polisi di tuntut mengembangkan penegakkan hukumnya sendiri. Dengan teori deskresi dan gambaran praktek pengungkapan jaringan narkotika. Polri diharapkan makin memacu anggota untuk meningkatkan kualitas sumber daya manusianya, meningkatkan pengawasan kinerja di lapangan, agar pelaksanaan diskresi tetap dijalur legal. Dengan demikian akan tumbuh kepercayaan masyarakat terhadap institusi kepolisian, yang dimana masyarakat secara sukarela menjadi mitra polisi dalam menciptakan keamanan dan ketertiban. Deskresi kepolisian pemberantasan narkotika secara teoritis akan memacu institusi kepolisian meningkatkan intelektualitas anggotanya agar menggunakan akal sehat dalam bertindak. Peredaran gelap narkotika dan korupsi adalah kejahatan berdimensi baru, yang memerlukan penanganan serius. Rumusan masalah dalam penelitian ini: bagaimana langkah-langkah polisi mengungkap jaringan narkoba dan bagaimana memberantas narkoba dengan konsep diskresi.Tipe penelitian yang dipergunakan adalah tipe penelitian empiris. Hasil pembahasan dalam penelitian ini sebagai berikut: Langkah-langkah polisi mengungkap jaringan narkoba diawali dengan: a).Surat panggilan, b). Penangkapan, Penggeledahan dan Penyitaan, c). Pemeriksaan dan d). Penahanan. Memberantas narkoba dengan konsep diskresi sebagai pelaksana dari satuan penyelidikan dan penyidikan terhadap kejahatan narkoba, satuan kerja narkoba bekerja atas dasar pakem ditetapkan oleh Kapolri berdasarkan laporan polisi. Petunjuk pelaksanaan atau Juklak dengan berbagai prinsip itulah yang menjadi langkah-langkah polisi dalam mengungkap jaringan narkoba. Langkah pengendalian dan pengawasan tidak hanya mengendalikan pengawasan dari pribadi polisi untuk secara dini melakukan seleksi atas tindakannya, tetapi juga sesama rekan dan keseriusan institusi kepolisian menindak polisi yang menyalahgunakanan diskresi, dengan dalih apapun. Untuk itu standar operasi menjadi lebih penting diwujudkan agar terdapat ukuran untuk meminimalkan penyimpangan diskresi. Kata Kunci: Diskresi; Narkotika; Kepolisian